Manufacturing method of arc-proof insulating gloves
By using modified nitrile latex and modified carbon nanotubes in arc-resistant insulated gloves, combined with knitting technology and vulcanization treatment, the problem of low oxygen index of existing gloves is solved, achieving higher performance glove preparation, suitable for A wider application of labor protection gloves.
Patent Information
- Application Number
- CN202411474191.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-11
AI Technical Summary
The existing arc-proof insulated gloves have a low oxygen index, which limits their use areas and cannot meet the higher demand in the field of labor protection glove technology.
Modified nitrile latex is used as the impregnation glue, and modified carbon nanotubes are added thereto. By knitting an arc-resistant jacket and inner liner, and vulcanizing it in an oven, it has excellent flame retardant, arc-resistant and heat-resistant properties. Gloves.
It significantly improves the flame retardancy, arc resistance and heat resistance of gloves, and has long-term and stable performance, and is suitable for a wider range of labor protection glove applications.
Smart Images

Figure BDA0005095573490000041 
Figure BDA0005095573490000042 
Figure BDA0005095573490000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of labor protection gloves, and in particular, relates to a method for manufacturing arc-proof insulating gloves. Background Art
[0002] Electric arc is a gas discharge phenomenon, which is a momentary spark produced by current passing through some insulating medium (such as air). At present, electric arc is generated in industries such as construction, machinery manufacturing, welding equipment and brazing equipment manufacturing, electrical equipment manufacturing, transportation equipment manufacturing, and repair and maintenance. When an electric arc occurs, huge energy is released in a very short time. The hazards of electric arc mainly include the following aspects: burns, damage to hearing, vision and respiratory system, etc.
[0003] In power work, relevant practitioners often encounter arc phenomena. As long as the arc magnitude is 1-2, it will cause 2nd degree burns to human skin. Wearing arc-proof insulating gloves can reduce hand injuries by about 70%. It can be seen that the importance of suitable arc-proof insulating gloves cannot be underestimated. Arc-proof insulating gloves are a kind of personal protective equipment designed to protect hands from arc damage. They are usually made of special fabrics and can provide a certain degree of heat insulation and fire protection. At present, the outer surface of arc-proof insulating gloves is covered with nitrile latex. Nitrile latex does not contain protein and meets the properties of wear resistance, anti-slip, oil resistance, puncture resistance and solvent resistance. However, the oxygen index of ordinary nitrile latex is low, which limits its use field. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of labor protection gloves technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a method for manufacturing arc-proof insulating gloves.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for manufacturing arc-proof insulating gloves comprises the following steps:
[0007] A1. Knitted arc-resistant outer shell and inner liner. First, put the inner liner on the hand model of the required specifications, apply adhesive, and then put the outer shell on the hand model. Let it stand for 12 hours until the adhesive is completely solidified to obtain the gloves to be dipped;
[0008] A2, heat and melt the modified nitrile latex into an emulsion-like slurry, then preheat the gloves to be dipped in step A1, soak them in the slurry, put them into an oven for vulcanization for 5-6 hours, the vulcanization temperature is 80-90°C, and after the vulcanization is completed, demoulding is performed to obtain arc-proof insulating gloves.
[0009] Furthermore, the number of needles of the arc-resistant jacket is 7, 10, 13, 15 and 18.
[0010] Furthermore, the number of needles knitted in the liner is 7, 10, 13, 15 and 18.
[0011] Furthermore, the yarn used in the arc-resistant jacket is aramid 1313 fiber.
[0012] Furthermore, the yarn used in the liner is made by blending cotton fiber and acrylic fiber in a mass ratio of 2:1.
[0013] The arc-resistant jacket is made of aramid 1313 fiber, which has significantly better mechanical properties and flame retardant properties than other ordinary fibers. By soaking in modified nitrile latex, the protective gloves are given oil-proof and corrosion-resistant properties; cotton fiber and acrylic fiber give the gloves a certain degree of comfort and moisture absorption.
[0014] Further, the modified nitrile latex is prepared by the following steps:
[0015] Magnesium oxide, sulfur, dispersant, vulcanization accelerator and antioxidant are put into a vulcanization ball mill, mixed evenly and ball milled. After ball milling, nitrile latex (solid content 50%-55%), modified carbon nanotubes and initiator are added for pre-vulcanization to obtain modified nitrile latex.
[0016] Furthermore, the raw materials are calculated in parts by weight as follows: 4-8 parts of magnesium oxide, 3-5 parts of sulfur, 2-4 parts of dispersant, 0.5-1.5 parts of vulcanization accelerator, 3-9 parts of antioxidant, 120-150 parts of nitrile latex, 15-25 parts of modified carbon nanotubes, and 0.1-0.3 parts of initiator.
[0017] Furthermore, the dispersant is one of sodium methylene bis-naphthalene sulfonate and sodium dibutyl naphthalene sulfonate.
[0018] Furthermore, the vulcanization accelerator is one of tetramethylthiuram disulfide and thiram.
[0019] Furthermore, the antioxidant is prepared by compounding antioxidant 1010 and antioxidant 618 in a mass ratio of 2:1.
[0020] Furthermore, the initiator is one of cumene hydroperoxide and tert-butyl hydroperoxide.
[0021] The antioxidants are hindered phenol antioxidants and phosphite auxiliary antioxidants, which can play a synergistic role and greatly enhance the antioxidant properties of nitrile latex.
[0022] Furthermore, the modified carbon nanotubes are prepared by the following steps:
[0023] S1. Mix 1,3-bis(aminopropyl)tetramethyldisiloxane and toluene, add them into a three-necked round-bottom flask equipped with a thermometer, a magnetic stirring system and a spherical condenser, add formaldehyde solution (mass fraction 14%) dropwise under ice-water bath conditions, and continue stirring for 30 minutes, then add 4-hydroxystyrene, control the reaction temperature to 65°C, reflux reaction for 8 hours, and complete the reaction. Cool to room temperature, remove the solvent by rotary evaporation, and then purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two is 2:1), remove the eluent by rotary evaporation to obtain an intermediate; the ratio of the amount of 1,3-bis(aminopropyl)tetramethyldisiloxane, toluene, formaldehyde solution, and 4-hydroxystyrene is 25.4g:100mL:10mL:11.9g;
[0024] 1,3-bis(aminopropyl)tetramethyldisiloxane reacts with 4-hydroxystyrene, and by controlling the molar ratio of the two to be close to 1:1 and a slight excess of 1,3-bis(aminopropyl)tetramethyldisiloxane, only one amino group on 1,3-bis(aminopropyl)tetramethyldisiloxane participates in the reaction to obtain an intermediate; the specific reaction process is as follows:
[0025]
[0026] S2. In a three-necked flask equipped with a stirring device, the carboxylated carbon nanotubes were mixed with N,N-dimethylformamide (DMF), and magnetically stirred for 3 hours to make the carboxylated carbon nanotubes evenly dispersed. The intermediate and dicyclohexylcarbodiimide (DCC, a dehydrating agent) were added in sequence, and after stirring evenly, the mixture was placed in a 60°C water bath for 3 hours for ultrasonication, and then the water bath was removed and magnetically stirred for 6 hours at room temperature. After the reaction was completed, the mixture was filtered, washed with anhydrous ethanol for 3-4 times, dried, and ground to obtain modified carbon nanotubes; the ratio of the amount of carboxylated carbon nanotubes, N,N-dimethylformamide, intermediate, and dicyclohexylcarbodiimide was 1g:100mL:10.5g:19.6g;
[0027] Under the action of DCC, -COOH on the surface of carboxylated carbon nanotubes undergoes an amidation reaction with -NH2 on the intermediate, and organic molecules are grafted on the surface of carbon nanotubes to obtain modified carbon nanotubes. The specific reaction process is as follows:
[0028]
[0029] The prepared modified carbon nanotubes are grafted with organic molecular chains through chemical bonding, that is, an organic layer is formed on the surface thereof, which can greatly improve the interfacial compatibility between the carbon nanotubes and the nitrile latex, thereby promoting the uniform dispersion of the modified carbon nanotubes in the nitrile latex, making the electrical properties of the carbon nanotubes fully exerted, reducing the risk of arc explosion caused by static electricity generated by friction of the gloves, and enhancing the arc resistance effect of the gloves. In addition, the modified carbon nanotubes also contain -Si-O-Si-chain segments, benzoxazine and carbon-carbon double bond structures, which are good flame retardant and smoke suppression components, which can not only improve the flame retardant properties of the nitrile matrix, but also have a certain smoke suppression effect; moreover, since the Si-O bond has a higher bond energy, it can improve the heat resistance of the matrix to a certain extent; the introduced benzoxazine can further enhance the heat resistance of the matrix; finally, the carbon-carbon double bond at one end of the modified carbon nanotube can produce a chemical bond with the matrix under the action of the initiator, further improving the compatibility of the modified carbon nanotube with the matrix, and improving the stability of the modified carbon nanotube;
[0030] It should be added that carbon nanotubes grafted with organic molecular chains can effectively prevent the migration and seepage of organic molecules, ensuring the long-term stability of various performance properties.
[0031] Furthermore, the carboxylated carbon nanotubes are prepared by the following steps:
[0032] The carbon nanotubes are placed in a conical flask, and then mixed acid is added, and ultrasonic treatment is performed in a water bath at 55°C for 6 hours. After the mixture is cooled to room temperature, deionized water is added for dilution, centrifugation is performed, and the mixture is washed with anhydrous ethanol and deionized water for 4-5 times in sequence, dried, and ground to obtain carboxylated carbon nanotubes; the mixed acid is a mixture of concentrated sulfuric acid with a mass fraction of 98% and concentrated hydrochloric acid with a mass fraction of 38.8% in a volume ratio of 4:1; the ratio of the amount of carbon nanotubes to the mixed acid is 1g:100mL;
[0033] By subjecting carbon nanotubes to ultrasonic shearing and oxidation treatment with strong acid, a certain number of carboxyl active groups can be introduced into the side walls and tops of the carbon nanotubes, thus laying the foundation for reaction sites for subsequent chemical reactions.
[0034] Beneficial effects of the present invention:
[0035] 1. The gloves prepared by the present invention include a knitted liner and a knitted arc-resistant outer shell, wherein the knitted arc-resistant outer shell can give the gloves excellent flame retardancy; the knitted liner can give the gloves a certain degree of comfort and moisture absorption performance;
[0036] 2. Using nitrile latex as dipping glue and adding modified carbon nanotubes to modify it not only further enhances the flame retardant properties of the gloves, but also enhances the heat resistance and arc resistance of the gloves, and the performance is long-lasting and stable;
[0037] 3. The compound antioxidant added to the nitrile latex can play a synergistic role and greatly enhance the antioxidant properties of the nitrile latex;
[0038] Therefore, the gloves prepared by the present invention have stable and efficient flame retardancy and arc resistance, good hygroscopicity, and comfortable hand feel, and have important application value in the technical field of labor protection gloves. DETAILED DESCRIPTION
[0039] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Embodiment 1
[0041] Preparation of carboxylated carbon nanotubes:
[0042] 1 g of carbon nanotubes was placed in a conical flask, and then 100 mL of concentrated sulfuric acid (mass fraction 98%) and concentrated hydrochloric acid (mass fraction 38.8%) were added in a volume ratio of 4:1 to obtain a mixed acid, and the mixture was ultrasonically treated in a 55°C water bath for 6 h. After the mixture was cooled to room temperature, deionized water was added to dilute it, centrifuged, and washed with anhydrous ethanol and deionized water for 4 times in sequence, dried, and ground to obtain carboxylated carbon nanotubes.
[0043] Embodiment 2
[0044] Preparation of modified carbon nanotubes:
[0045] S1. Mix 25.4 g of 1,3-bis(aminopropyl)tetramethyldisiloxane and 100 mL of toluene, add the mixture into a three-necked round-bottom flask equipped with a thermometer, a magnetic stirring system and a spherical condenser, add 10 mL of formaldehyde solution (mass fraction 14%) dropwise in an ice-water bath, and continue stirring for 30 min, then add 11.9 g of 4-hydroxystyrene, control the reaction temperature to 65 ° C, reflux for 8 h, complete the reaction, cool to room temperature, remove the solvent by rotary evaporation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 2:1), remove the eluent by rotary evaporation to obtain an intermediate;
[0046] S2. In a three-necked flask equipped with a stirring device, 1 g of the carboxylated carbon nanotubes prepared in Example 1 was mixed with 100 mL of N,N-dimethylformamide and magnetically stirred for 3 h to uniformly disperse the carboxylated carbon nanotubes. 10.5 g of the intermediate and 19.6 g of dicyclohexylcarbodiimide were added in sequence and stirred evenly. The mixture was placed in a 60°C water bath and ultrasonicated for 3 h. The water bath was removed and magnetically stirred for 6 h at room temperature. After the reaction was completed, the mixture was filtered and washed with anhydrous ethanol for 3 times, dried and ground to obtain modified carbon nanotubes.
[0047] Embodiment 3
[0048] Preparation of modified carbon nanotubes:
[0049] S1. Mix 50.8 g of 1,3-bis(aminopropyl)tetramethyldisiloxane and 200 mL of toluene, add the mixture into a three-necked round-bottom flask equipped with a thermometer, a magnetic stirring system and a spherical condenser, add 20 mL of formaldehyde solution (mass fraction 14%) dropwise in an ice-water bath, and continue stirring for 30 min, then add 23.8 g of 4-hydroxystyrene, control the reaction temperature to 65 ° C, reflux for 8 h, complete the reaction, cool to room temperature, remove the solvent by rotary evaporation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 2:1), remove the eluent by rotary evaporation to obtain an intermediate;
[0050] S2. In a three-necked flask equipped with a stirring device, 2 g of the carboxylated carbon nanotubes prepared in Example 1 was mixed with 200 mL of N,N-dimethylformamide, and magnetically stirred for 3 h to uniformly disperse the carboxylated carbon nanotubes. 21 g of the intermediate and 39.2 g of dicyclohexylcarbodiimide were added in sequence, and after uniform stirring, the mixture was placed in a 60°C water bath for ultrasonic treatment for 3 h, and then the water bath was removed and magnetically stirred for 6 h at room temperature. After the reaction was completed, the mixture was filtered, washed with anhydrous ethanol for 4 times, dried, and ground to obtain modified carbon nanotubes.
[0051] Embodiment 4
[0052] Preparation of modified nitrile latex:
[0053] 4 g of magnesium oxide, 3 g of sulfur, 2 g of sodium methylenebisnaphthalene sulfonate, 0.5 g of tetramethylthiuram disulfide and 3 g of antioxidant (prepared by compounding 2 g of antioxidant 1010 and 1 g of antioxidant 618) were put into a sulfurization ball mill, mixed evenly, and ball-milled. After ball milling, 120 g of nitrile latex (solid content 50%), 15 g of modified carbon nanotubes prepared in Example 2 and 0.1 g of isopropylbenzene hydroperoxide were added for pre-sulfurization to obtain modified nitrile latex.
[0054] Embodiment 5
[0055] Preparation of modified nitrile latex:
[0056] 6 g of magnesium oxide, 4 g of sulfur, 3 g of sodium methylenebisnaphthalene sulfonate, 1 g of tetramethylthiuram disulfide and 6 g of antioxidant (prepared by compounding 4 g of antioxidant 1010 and 2 g of antioxidant 618) were put into a sulfurization ball mill, mixed evenly, and ball-milled. After ball milling, 135 g of nitrile latex (solid content 55%), 20 g of modified carbon nanotubes prepared in Example 3 and 0.2 g of isopropylbenzene hydroperoxide were added for pre-sulfurization to obtain modified nitrile latex.
[0057] Embodiment 6
[0058] Preparation of modified nitrile latex:
[0059] 8 g of magnesium oxide, 5 g of sulfur, 4 g of sodium dibutylnaphthalene sulfonate, 1.5 g of thiram and 9 g of antioxidant (prepared by compounding 6 g of antioxidant 1010 and 3 g of antioxidant 618) are put into a vulcanization ball mill, mixed evenly, and ball-milled. After ball milling, 150 g of nitrile latex (solid content 55%), 25 g of modified carbon nanotubes prepared in Example 3 and 0.3 g of tert-butyl hydroperoxide are added for pre-vulcanization to obtain modified nitrile latex.
[0060] Embodiment 7
[0061] A1. Knitted arc-resistant outer shell and inner liner. First, put the inner liner on the hand model of the required specifications, apply adhesive, and then put the outer shell on the hand model. Let it stand for 12 hours until the adhesive is completely solidified to obtain the gloves to be dipped;
[0062] A2, heating and melting the modified nitrile latex prepared in Example 4 into an emulsion-like slurry, then preheating the gloves to be dipped in step A1, soaking them in the slurry, and vulcanizing them in an oven for 5 hours at a vulcanization temperature of 80° C. After the vulcanization is completed, demoulding is performed to obtain arc-proof insulating gloves;
[0063] The number of needles of the arc-resistant jacket is 7;
[0064] The number of needles knitted in the liner is 7;
[0065] The yarn used in the arc-resistant jacket is aramid 1313 fiber;
[0066] The yarn used in the liner is made by blending cotton fiber and acrylic fiber in a mass ratio of 2:1.
[0067] Embodiment 8
[0068] A1. Knitted arc-resistant outer shell and inner liner. First, put the inner liner on the hand model of the required specifications, apply adhesive, and then put the outer shell on the hand model. Let it stand for 12 hours until the adhesive is completely solidified to obtain the gloves to be dipped;
[0069] A2, heating and melting the modified nitrile latex prepared in Example 6 into an emulsion-like slurry, then preheating the gloves to be dipped in step A1, soaking them in the slurry, and vulcanizing them in an oven for 5 hours at a vulcanization temperature of 80° C. After the vulcanization is completed, demoulding is performed to obtain arc-proof insulating gloves;
[0070] The arc-resistant jacket has 13 needles;
[0071] The number of needles knitted in the liner is 13;
[0072] The yarn used in the arc-resistant jacket is aramid 1313 fiber;
[0073] The yarn used in the liner is made by blending cotton fiber and acrylic fiber in a mass ratio of 2:1.
[0074] Embodiment 9
[0075] A1. Knitted arc-resistant outer shell and inner liner. First, put the inner liner on the hand model of the required specifications, apply adhesive, and then put the outer shell on the hand model. Let it stand for 12 hours until the adhesive is completely solidified to obtain the gloves to be dipped;
[0076] A2, heating and melting the modified nitrile latex prepared in Example 7 into an emulsion-like slurry, then preheating the gloves to be dipped in step A1, soaking them in the slurry, and vulcanizing them in an oven for 6 hours at a vulcanization temperature of 90° C. After the vulcanization is completed, demoulding is performed to obtain arc-proof insulating gloves;
[0077] The arc-resistant jacket has 18 needles;
[0078] The number of needles knitted in the liner is 18;
[0079] The yarn used in the arc-resistant jacket is aramid 1313 fiber;
[0080] The yarn used in the liner is made by blending cotton fiber and acrylic fiber in a mass ratio of 2:1.
[0081] Comparative Example 1
[0082] Ordinary carbon nanotubes of the same mass were used to replace the modified carbon nanotubes in Example 6, and the remaining steps were the same as those in Example 6 to prepare nitrile latex.
[0083] Comparative Example 2
[0084] Commercially available nitrile latex was used.
[0085] Comparative Example 3
[0086] The nitrile latex prepared in Comparative Example 1 was used to replace the modified nitrile latex in Example 9, and the remaining steps were the same as those in Example 9.
[0087] Comparative Example 4
[0088] Use commercially available arc-proof gloves.
[0089] The examples 4, 5, 6 and the comparative examples 1 and 2 were placed in an oven at 100°C for 6 hours to fully vulcanize them, and the following performance tests were performed:
[0090] The tensile strength was determined using the national standard GB / T 528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”;
[0091] The sample was placed in a xenon lamp aging test chamber for accelerated aging for 30 days. The aging conditions were air atmosphere, xenon lamp wavelength 280-800nm, and irradiation intensity 550W / m 2 , test the tensile strength of the sample after aging (GB / T 528-2009), and calculate the tensile strength retention rate; tensile strength retention rate = tensile strength after test / tensile strength before test × 100%;
[0092] After the sample was left to stand at 160°C for 48 hours, the tensile strength of the sample after heat aging was tested (GB / T528-2009), and the tensile strength retention rate was calculated;
[0093] The measured results are shown in Table 1:
[0094] Table 1
[0095]
[0096]
[0097] The gloves of Examples 7, 8, 9 and Comparative Examples 3 and 4 were subjected to the following performance tests:
[0098] The arc resistance performance is measured using the ASTM F 1506 standard;
[0099] The flame retardant properties were determined by vertical burning test using ASTM D-6413 standard;
[0100] The measured results are shown in Table 2:
[0101] Table 2
[0102]
[0103] It can be seen from the above two tables that the modified nitrile latex prepared in the embodiment of the present invention has higher mechanical properties, aging resistance and heat resistance than the control example, and the prepared gloves have excellent flame retardancy and arc resistance, and have important application value in the field of labor protection gloves technology.
[0104] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0105] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for manufacturing arc-proof insulating gloves, characterized in that: The following steps are involved: A1. Knitted arc-resistant outer shell and inner liner. First, put the inner liner on the hand model of the required specifications, apply adhesive, and then put the outer shell on the hand model. Let it stand for 12 hours until the adhesive is completely solidified to obtain the gloves to be dipped; A2, heat and melt the modified nitrile latex into an emulsion-like slurry, then preheat the gloves to be dipped in step A1, soak them in the slurry, put them into an oven for vulcanization for 5-6 hours, the vulcanization temperature is 80-90°C, and after the vulcanization is completed, demoulding is performed to obtain arc-proof insulating gloves.
2. The method for manufacturing arc-proof insulating gloves according to claim 1, characterized in that: The modified nitrile latex is prepared by the following steps: Magnesium oxide, sulfur, dispersant, vulcanization accelerator and antioxidant are put into a vulcanization ball mill tank, mixed evenly, and ball milled. After ball milling, nitrile latex, modified carbon nanotubes and initiator are added for pre-vulcanization to obtain modified nitrile latex.
3. The method for manufacturing arc-proof insulating gloves according to claim 2, characterized in that: The modified carbon nanotubes are prepared by the following steps: S1. Mix 1,3-bis(aminopropyl)tetramethyldisiloxane and toluene, add formaldehyde solution dropwise, and continue stirring for 30 min, then add 4-hydroxystyrene, reflux at 65° C. for 8 h, and after the reaction is completed, cool to room temperature, perform rotary evaporation, purify by column chromatography, and perform rotary evaporation to obtain an intermediate; S2. Mix the carboxylated carbon nanotubes with N,N-dimethylformamide, and stir magnetically for 3 hours. Then add the intermediate and dicyclohexylcarbodiimide in sequence. After stirring evenly, place in a 60°C water bath for 3 hours of ultrasonic treatment. Then remove the water bath and stir magnetically for 6 hours at room temperature. After the reaction is completed, filter, wash, dry and grind to obtain modified carbon nanotubes.
4. The method for manufacturing arc-proof insulating gloves according to claim 3, characterized in that: In step S1, the ratio of the amount of 1,3-bis(aminopropyl)tetramethyldisiloxane, toluene, formaldehyde solution, and 4-hydroxystyrene is 25.4 g:100 mL:10 mL:11.9 g.
5. The method for manufacturing arc-proof insulating gloves according to claim 3, characterized in that: In step S2, the ratio of the amount of carboxylated carbon nanotubes, N,N-dimethylformamide, intermediate, and dicyclohexylcarbodiimide is 1 g:100 mL:10.5 g:19.6 g.
6. The method for manufacturing arc-proof insulating gloves according to claim 2, characterized in that: The raw materials are calculated in parts by weight as follows: 4-8 parts of magnesium oxide, 3-5 parts of sulfur, 2-4 parts of dispersant, 0.5-1.5 parts of vulcanization accelerator, 3-9 parts of antioxidant, 120-150 parts of nitrile latex, 15-25 parts of modified carbon nanotubes, and 0.1-0.3 parts of initiator.
7. The method for manufacturing arc-proof insulating gloves according to claim 2, characterized in that: The antioxidant is prepared by compounding antioxidant 1010 and antioxidant 618 in a mass ratio of 2:
1.
8. The method for manufacturing arc-proof insulating gloves according to claim 1, characterized in that: The yarn used in the arc-resistant jacket is aramid 1313 fiber.
9. The method for manufacturing arc-proof insulating gloves according to claim 1, characterized in that: The yarn used in the liner is made by blending cotton fiber and acrylic fiber in a mass ratio of 2:1.